Examination of the current and idel organisational culture and leadership elements at the municipalities of the North Great Plain region - Matkó, Andrea (Acta Agraria Debreceniensis, 2013)
The connection between organizational culture and leadership has been examined by several researchers (Schein, Schmircik, Bass) and it is proven that there is a link between them. The leader shapes the organizational culture and at the same time the organizational culture shapes the leader too. The middle managers of local governments place the major emphasis on the dimension of goal orientation for the future. From the leadership perspective they find charismatic, goal and team oriented leadership necessary for the future. The local governments have to answer the challenges of the rapidly changing environment. Quick responses and adjustments are only possible if the leader possesses a clear future vision and not only sets short-term goals but plans for the future and estimates the necessities on the long run. It is important to have a leadership with utmost dedication to the organization and to the objectives of the organization. The leaders must raise the interests of the employees, involve them in the process of setting goals and in finding ways to meet those goals, and that the employees should no longer strive to realize their own personal ambitions but focus on the common objectives. This brought transformational leadership to light. The leader establishes and shapes the organizational culture but the individuals and teams working for the organization have impact on the organizational culture as well. This becomes apparent in the organizational culture as middle managers would place the major emphasis on performance orientation. Performance orientation is a dominant motivation based on excellence, hard work, pre-calculated risk, fore planning, goal orientation and regular feedback, which shapes the leadership too, as the leader has to change as well, in order to run the organization. Scheins’ standpoint reflects the best the relationship between the organizational culture and the leadership. Schein claims that organizational culture and leadership are interwoven phenomena, as the leader shapes the culture but after a while the organizational culture itself shapes the leader too.